Do benevolent and altruistic supervisors have higher postgraduate supervision throughput? The contributions of individual motivational values to South African postgraduate supervision throughput - Callaghan, C.W. (South African Journal of Higher Education, 2020)
This study seeks to understand how the individual values of a supervisor potentially influence their masters and doctoral supervision throughput. Grounded in Schwartz’s theory of basic human values, the objective of the article is to test theory that predicts different effects of different value orientations on postgraduate supervision throughput, using a census sample of a large South African university. What is not clear from the literature is whether self-transcendent values (associated with benevolence and “caring” values) or self-enhancement values (associated with prioritisation of the self and achievement values) increase an individual’s postgraduate supervision throughput. According to Schwartz’s theory, however, self-transcendent and self-enhancement values are oppositional, in that the higher an individual’s endowment is in one, the lower it is in that of the other. What is also lacking in the literature is knowledge of whether innovative openness to change values or their oppositional non-innovative conservation values enable postgraduate supervision throughput. Ordinary least squares are used to test these hypotheses across five different faculties, representing a clustering of similar academic fields. According to the results of tests across the broad faculty fields of Engineering, Commerce, Humanities, Health Sciences, and Science, it is not the individual values associated with benevolence or caring that facilitate postgraduate supervision throughput, but rather those related to the prioritisation of the self over others, such as power, achievement and hedonism. Similarly, innovation-related values associated with openness to change are largely insignificant in their associations with postgraduate supervision throughput. The implications of the findings are discussed and recommendations are derived for theory and practice.